2007
DOI: 10.1007/s00127-007-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for emotional and behavioural problems amongst 5–11-year-old school children in Karachi, Pakistan

Abstract: In the present study, prevalence of child mental health problems was higher than reported in studies from other countries. Prevalence was higher amongst children attending community schools. Consistent with most studies, male children were at a higher risk than females. There is a need for developing programs to train, sensitise and mobilize teachers and parents regarding child's psychological, emotional and behavioural problems with special attention to community schools. Since the male child is at a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 22 publications
6
81
3
1
Order By: Relevance
“…Socio--emotional development included two main domains: behavioral/emotional problems, assessed with the Strengths and Difficulties Questionnaire (SDQ) 15,16 and anxiety with the Spence Children's Anxiety Scale (SCAS). 17 The SDQ is parent administered and has been validated in Pakistan; 20 questions inquire about the child's difficulties in four areas: emotional, conduct problems, hyperactivity, peer problems, and pro--social.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio--emotional development included two main domains: behavioral/emotional problems, assessed with the Strengths and Difficulties Questionnaire (SDQ) 15,16 and anxiety with the Spence Children's Anxiety Scale (SCAS). 17 The SDQ is parent administered and has been validated in Pakistan; 20 questions inquire about the child's difficulties in four areas: emotional, conduct problems, hyperactivity, peer problems, and pro--social.…”
Section: Methodsmentioning
confidence: 99%
“…17 The SDQ is parent administered and has been validated in Pakistan; 20 questions inquire about the child's difficulties in four areas: emotional, conduct problems, hyperactivity, peer problems, and pro--social. 15,16 The total difficulties score is generated by summing the problem scale scores, ranging from 0 to 40. The SCAS is also parent administered and comprises of six different subscales in addition to an overall anxiety score: panic and agoraphobia, separation anxiety, physical injury fears, social phobia, obsessive--compulsive problems, and generalized anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Urdu version of the SDQ (SDQ-U) has been used in several studies in Pakistan [22][23][24][25], to our knowledge no studies have examined its factor structure. Thus, it remains unclear at this time whether the factor structure of the SDQ as determined by Goodman [7] can be applied to adolescents in Pakistan.…”
Section: Instrumentsmentioning
confidence: 99%
“…A summary of significant international epidemiological studies concluded that the rate and range of psychiatric symptoms in children is similar in lower-and higher-income countries (Fayyad et al, 2001). However, the prevalence of child mental health problems in Pakistan is higher than has been reported in studies from other countries (Syed et al, 2007a). Research in the area of understanding the psychopathology of mental disorders in children in our cultural context needs to be explored (Nikapota, 1991).…”
Section: Research and Auditmentioning
confidence: 99%